Reading rainbow. 4 classic episodes featuring Animal cafe [videorecording (DVD)]. - Short, Martin, 1950-; Radner, Gilda; Diller, Phyllis (Reading rainbow., 2015)
Take a look, it's in a book, a Reading Rainbow! For over 30 years, the beloved children's television series has been bringing stories to life. Hosted by acclaimed actor LeVar Burton, journey to exciting places and build a lasting connection with books.